Isoalantolactone (IAL) Regulates Neuro-Inflammation and Neuronal Apoptosis to Curb Pathology of Parkinson’s Disease - Dewei He; Yanting Liu; Jie Li; Hefei Wang; Bojian Ye; Yuan He; Zhe Li; Xiyu Gao; Shoupeng Fu; Dianfeng Liu (Cells, 2022)
Parkinson’s disease (PD) is a neurodegenerative disease in which neuronal apoptosis and associated inflammation are involved in its pathogenesis. However, there is still no specific treatment that can stop PD progression. Isoalantolactone (IAL) plays a role in many inflammation-related diseases. However, its effect and mechanism in PD remain unclear. In this study, results showed that IAL administration ameliorated 1-methyl-4-phenyl-1, 2, 3, 6-tetrahydropyridine (MPTP)-induced PD-related pathological impairment and decreased motor activity in mice. Results from in vitro mechanistic studies showed that IAL regulated apoptosis-related proteins by activating the AKT/Nrf2 pathway, thereby suppressing the apoptosis of SN4741 cells induced by N-methyl-4-phenylpyridinium Iodide (MPP+). On the other hand, IAL inhibited LPS-induced release of pro-inflammatory mediators in BV2 cells by activating the AKT/Nrf2/HO-1 pathway and inhibiting the NF-κB pathway. In addition, IAL protected SN4741 from microglial activation-mediated neurotoxicity. Taken together, these results highlight the beneficial role of IAL as a novel therapy and potential PD drug due to its pharmacological profile.